2015
DOI: 10.1016/j.jqsrt.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Fast linear solver for radiative transport equation with multiple right hand sides in diffuse optical tomography

Abstract: It is well known that radiative transfer equation (RTE) provides more accurate tomographic results than its diffusion approximation (DA). However, RTE-based tomographic reconstruction codes have limited applicability in practice due to their high computational cost. In this article, we propose a new efficient method for solving the RTE forward problem with multiple light sources in an all-at-once manner instead of solving it for each source separately. To this end, we introduce here a novel linear solver calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…97,101 Even with current advanced computer technology, however, the heavy computational load is still the biggest drawback with the RTE. A variety of fast solvers of the RTE have been proposed, [102][103][104][105] and among these a hybrid model-based the RTE and DE is one of the most promising approaches. The hybrid model is based on the idea that the DE is an accurate model for measurements far from a light source.…”
Section: Hybrid Model Based On the Radiative Transfer Equation And Thmentioning
confidence: 99%
“…97,101 Even with current advanced computer technology, however, the heavy computational load is still the biggest drawback with the RTE. A variety of fast solvers of the RTE have been proposed, [102][103][104][105] and among these a hybrid model-based the RTE and DE is one of the most promising approaches. The hybrid model is based on the idea that the DE is an accurate model for measurements far from a light source.…”
Section: Hybrid Model Based On the Radiative Transfer Equation And Thmentioning
confidence: 99%
“…However, due to computationally expensive nature of these models, utilizing them in high dimensional tomographic inverse problems is often not feasible in practice. Although many computational challenges related to these models have been overcome by development of computational resources and numerical methods, such as usage of efficient parallel computing [39] or preconditioned Krylov subspace methods [40,41], their utilization is still limited in tomographic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The other components are expanded by finite series of Legendre polynomials and used as the phase function in the dEM. The dEM has been widely employed in the field of biomedical optics since Klose and coworkers have introduced from the field of astrophysics [18][19][20][21][22]. It has been shown that the numerical solutions of the dEM agree with those of the RTE while the number of the discrete angular directions is reduced to approximately one-sixth of the required number for the RTE-calculations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the numerical solutions of the dEM agree with those of the RTE while the number of the discrete angular directions is reduced to approximately one-sixth of the required number for the RTE-calculations. Nevertheless, a validity of the dEM is still unclear; Klose and coworkers showed that the second order dEM can provide the accurate results the same as the RTE [21], while Jia and coworkers stated that the zeroth order dEM is sufficient [22], and Boulet and coworkers employed the zeroth and first order dEM [20]. These differences probably come from the fact that the validity of the dEM depends on the SD distances, times after light incidence, and the optical properties, like the validity of the PDE.…”
Section: Introductionmentioning
confidence: 99%